Immersive virtual reality learning environments for higher education: A student acceptance study - Stefan Aufenanger; Jasmin Bastian; Glória Bastos; Maria Castelhano; Célia Dias-Ferreira; Emmanuel Fokides; Damianos Gavalas; Vlasios Kasapakis; Androniki Agelada; Apostolos Kostas; George Koutromanos; Gregory Makrides; et al. (Computers & Education: X Reality, 2025)
The study investigates the integration of Virtual Reality Learning Environments (VRLEs) in academic teaching through the EU-funded ''REVEALING'' project. Researchers from Cyprus, Germany, Greece, Poland, and Portugal developed and evaluated five different immersive VRLEs, each focusing on diverse educational topics, including ancient Greek technology, sea urchin measurements, linear algebra, and historical expeditions. The study aims to determine effective instructional design principles for VRLEs and assess students' acceptance and learning outcomes.The VRLEs were designed based on literature-derived principles that emphasise ease of tool usage, authentic experiences, and continuous feedback. Students from the participating universities explored these VR environments, providing feedback through a standardized questionnaire on aspects like immersion, ease of use, motivation, and emotions.Results show that most participants positively engaged with the VRLEs, reporting high motivation and positive emotional responses, particularly for experiences involving interactivity. However, challenges like motion sickness and technical issues were noted, especially at one institution. The findings suggest that immersive VR experiences can significantly enhance motivation and engagement, but their effectiveness depends on careful alignment with pedagogical goals, design quality, and user experience considerations.